(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: The use of personal protective equipment can be burdensome and the risk of COVID-19 infection for this group is high. This study details to evaluate how prepared Health Care Workers consider themselves to be regarding the delivery of infection prevention and control procedures in their place of work. Method: This is a cross-sectional study conducted at Kathmandu Medical College Teaching Hospital in September 2020. A questionnaire was given to participants along with the information about the study. Service demand, skills, beliefs about capabilities, beliefs about consequences, intentions, environmental context and resources, social influences, emotion, WHO Wellbeing (over the last two weeks) were taken as dependent variables. Result: Out of 112 participants, 58(51.7%) were doctors and 54(48.3%) nurses; 65(58.1%) female and 47(41.9%) were male. The mean age was 31.2±4.1 y. Service demand was scored lowest (mean 0.7 out of 7) and beliefs about consequences were scored highest (mean 5.7 out of 7). Conclusion: Healthcare workers agreed that personal protective equipment at work is sufficiently effective to prevent the spread of COVID-19. They were not confident that the health care center at present can manage or can continue to manage the current patient surge related to COVID-19.